Developing a Tabletop Exercise to Test Community Resilience: Lessons from the Los Angeles County Community Disaster Resilience Project. (17th August 2015) - Chandra, Anita; Williams, Malcolm V.; Lopez, Christian; Tang, Jennifer; Eisenman, David; Magana, Aizita
Abstract: Objective: We aimed to develop and test a community resilience tabletop exercise to assess progress in community resilience and to provide an opportunity for quality improvement and capacity building. Methods: A tabletop exercise was developed for the Los Angeles County Community Disaster Resilience (LACCDR) project by using an extended heat wave scenario with health and infrastructure consequences. The tabletop was administered to preparedness only (control) and resilience (intervention) coalitions during the summer of 2014. Each exercise lasted approximately 2 hours. The coalitions and LACCDR study team members independently rated each exercise to assess 4 resilience levers (partnership, engagement, self-sufficiency, and education). Resilience coalitions received more detailed feedback in the form of recommendations for improvement. Results: The resilience coalitions performed the same or better than the preparedness coalitions on the partnership and self-sufficiency levers. Most coalitions did not have enough (both quantity and type) of the partner organizations needed for an escalating heat wave or changing conditions or enough engagement of organizations representing at-risk populations. Coalitions also lacked educational materials to cover topics as far ranging as heat to power outages to psychological impacts of disaster. Conclusion: A tabletop exercise can be used to stress and test resilience-based capacities, with particular attention to a community's ability to leverage a range of partnerships and other assets to confront a slowly evolving but multifactorial emergency. ( Disaster Med Public Health Preparedness . 2015;9:484–488)